Implementasi Pengaturan Hak Untuk Dilupakan Melalui Sistem Penghapusan Data Pribadi dan/atau Dokumen Elektronik Menurut Perspektif Hukum Positif di Indonesia - Taufik Ajiputera, Muhammad; Susetyo, Heru (Universitas Ekasakti, 2024)
The Internet revolutionized the information market by allowing people to access unlimited information with just a computer and a connection. Information on the internet is not only more accessible, but also eternal (Digital Eternity). Social media is not only used to communicate, but is also used for many negative things such as providing information that is incorrect, unethical, even violating legal regulations and disrupting public conversation. In simple terms, it is a spreading activity such as uploading and writing wrong or prohibited things that can harm other people. Therefore, Indonesia is looking for a way to adopt the European legal system regarding human rights, where the right is to maintain one's reputation as a human being worthy of living without the shadow of the past, so that the term Right to be Forgotten is found, which is defined as the right to obtain, automatically or upon request, the deletion of personal information, which is no longer useful, posted by the data owner himself, or a third party, even if the information was posted lawfully. This right will provide major freedoms to victims who feel disadvantaged by their personal data being distributed via electronic media. Currently, Indonesia has included a right-to-be-forgotten clause in several laws and regulations that have been approved, and the implementation system has even been regulated. However, there are still many problems that make it a little difficult to enforce this right, considering that Indonesia also has the right to an opinion and the right to know public information, so the implementation of the right to be forgotten is still often subject to criticism and is strangled by the right to remember/right to know.